Evaluation of allyl sulfides bearing methacrylate groups as addition-fragmentation chain transfer agents for low shrinkage dental composites. (5th December 2022) - Grob, Benjamin; Frieser, Benedikt; Liska, Robert; Catel, Yohann
Graphical abstract: Highlights: Synthesis of four novel polymerizable addition-fragmentation chain transfer agents. Preparation and evaluation of innovative low-shrinkage dental composites exhibiting excellent low shrinkage and mechanical properties. Influence of the incorporated methacrylate moiety on the glass transition, the mechanical properties, and the shrinkage stress of the assessed materials. Abstract: Polymerization shrinkage and the consequential shrinkage stress in methacrylate-based dental composites are crucial drawbacks for restorative dentistry. An effective way for the reduction of shrinkage stress is the incorporation of addition fragmentation chain transfer agents (AFCT agents). In this contribution, four novel polymerizable allyl sulfides were synthesized and evaluated in dental composites. Photo-DSC and DMTA measurements were performed to evaluate their influence on the polymerization rate and on the network homogeneity. Good to excellent shrinkage force values and mechanical properties were obtained for all AFCT based composites. Especially, the incorporation of AFCT agents containing multiple urethane and methacrylate moieties improved the mechanical properties. Hence, the incorporation of polymerizable and urethane-based allyl sulfides in dental composite is a promising strategy to obtain low shrinkage materials exhibiting high flexural strength and modulus.